Nanofiltration membrane concentration and separation method for ionic rare earth leachate
By reducing the pH value during the nanofiltration separation process of the rare earth leaching solution, the solubility of calcium sulfate is improved, and the problems of membrane pollution and flux performance attenuation are solved, efficient concentration and separation of the rare earth leaching solution is achieved, and the efficiency of rare earth extraction and enrichment is improved.
Patent Information
- Application Number
- CN202510074338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
During the nanofiltration separation process of rare earth leaching liquid, membrane pollution and filtration flux performance are easily affected, especially because membrane pollution problems caused by calcium ions are difficult to effectively solve.
By concentrating and separation of rare earth leaching liquid at lower pH conditions, the solubility of calcium sulfate is improved, the precipitation of contaminants on the surface of the membrane is avoided, and the effect of different membrane process parameters and feed liquid characteristics on calcium sulfate scale is analyzed in combination with the Hermia model.
Under low pH conditions, the solubility of calcium sulfate increases, which helps to increase the concentration ratio, and the positive electrical properties of the membrane surface increase, which helps to improve the retention of rare earth ions, thereby improving the efficient membrane concentration efficiency of rare earth leaching liquid, reducing equipment investment costs, and promoting the development of the rare earth mining industry.
Smart Images

Figure CN119824256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nanofiltration membrane concentration and separation method for ionic rare earth leaching solution, belonging to the technical field of membrane separation. Background Art
[0002] Weathering crust leaching type rare earth ore (also known as ion adsorption type rare earth ore) is an important source of rare earth, but the grade is extremely low, only 0.03% to 0.1%. The traditional industrial mining method is to use ammonium sulfate for in-situ leaching and ammonium bicarbonate precipitation for enrichment. This process faces some major challenges, including ammonia nitrogen pollution, difficulty in handling radioactive waste residues, and complexity of precipitation enrichment steps. Membrane separation technology is gradually attracting widespread attention due to its high efficiency, energy saving and ease of operation, and is regarded as a cutting-edge technology in the field of rare earth leachate concentration. As the core membrane material of this technology, its performance directly determines the separation effect. In particular, nanofiltration membranes are expected to achieve efficient recovery of rare earth ions with their excellent selectivity and higher membrane flux than permeation. However, in the process of rare earth leaching, a large amount of high-priced impurity ions are leached along with rare earth ions, among which calcium ions have the highest content. The calcium ion concentration in the rare earth leachate is about 0.15~0.40 g / L, and the saturated calcium ion concentration is about 0.59 g / L. Theoretically, after the volume of rare earth solution is concentrated to 26%-69% of the original solution, calcium salts will rapidly crystallize on the membrane surface, resulting in serious membrane pollution. The membrane flux will rapidly decay until the membrane pores are completely blocked. In the membrane concentration process of rare earth leachate, preventing calcium sulfate scaling is the key to improving the concentration multiple and efficiency of the leachate. Calcium ions and rare earth ions have similar ionic radius and hydration radius. The strategy of using pretreatment technologies such as ion exchange, chemical precipitation, and membrane separation to remove calcium ions to reduce membrane pollution is difficult to implement effectively in this system.
[0003] On the other hand, the Hermia model, as a semi-empirical model, describes four classic forms of membrane fouling: full pore plugging model, intermediate pore plugging model, standard pore plugging model and cake layer formation model [non-patent literature 1, 2]. However, in the concentration process of rare earth leachate, which contains multiple metal ions and is prone to membrane fouling, there are still unknowns in how to use the Hermin model to analyze the membrane fouling mechanism.
[0004] Non-patent literature 1: Field RW, Wu D, Howell JA, et al. Critical flux concept for microfiltration fouling [J]. Journal of Membrane Science, 1995,100(3): 259-272. Non-patent document 2: Gao MF, He QL, Dong HZ, et al. Identification of the coupled fouling mechanism involved in microfiltration of tobacco extractsliquid by multistage Hermia model [J]. Journal of Food Process Engineering, 2022, 45(2): 13961. Summary of the invention
[0005] The technical problem to be solved by the present invention is that during the nanofiltration separation of ionic rare earth leachate, membrane pollution and filtration flux performance are easily affected. The present invention proposes an improved concentration separation method, which can effectively increase the concentration of calcium sulfate under low pH conditions and avoid the precipitation of pollutants on the membrane surface.
[0006] A technical solution of the present invention is: A method for concentrating and separating an ionic rare earth leachate using a nanofiltration membrane comprises the following steps: The rare earth leaching solution is obtained, the pH value is lowered, and then the solution is concentrated using a nanofiltration membrane.
[0007] The rare earth ion concentration in the rare earth leaching solution is in the range of 10-1000 mg / L.
[0008] Rare earth ions refer to cations of one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium or yttrium.
[0009] The leaching solution also contains Ca 2+ 50-800 mg / L and / or Mg 2+ 200-3000mg / L.
[0010] Lowering the pH means lowering the pH to 0.5-4, preferably 0.5-3.
[0011] In the process of lowering the pH, sulfuric acid, hydrochloric acid or nitric acid is used for adjustment.
[0012] The pressure range during the concentration process of the nanofiltration membrane is 3-10 bar.
[0013] Another technical solution of the present invention is: A method for predicting membrane fouling types during nanofiltration membrane concentration of ionic rare earth leachate, wherein the membrane fouling type is determined by fitting nanofiltration membrane flux attenuation curve data through a Hermia fouling model and taking the fouling type with the maximum correlation coefficient value; the method comprises the following steps: when the pH value range of the leachate is 5-6, it is standard pore blockage; if the pH value range of the leachate is 2.5-3.5, it is intermediate pore blockage; if the pH value range of the leachate is 0.8-1.2, it is complete pore blockage.
[0014] Another technical solution of the present invention is: A method for determining membrane contamination during the concentration of an ionic rare earth leaching solution by a nanofiltration membrane, the method being used to determine the surface contamination amount of the nanofiltration membrane after concentration; comprising the following steps: The pollutants remaining on the surface of the concentrated nanofiltration membrane are dissolved in water, and the content of pollutant ions in the water is detected; In addition, the nanofiltration membrane is immersed in the same raw material liquid, and then immersed in water to detect the content of pollutant ions in the water. If the pollutant ions can be detected, it is determined that there is ion adsorption contamination on the membrane surface, and if the pollutant ions cannot be detected, it is determined that there is no ion adsorption contamination on the membrane surface.
[0015] The pollutant is calcium sulfate, and the pollutant ions are calcium ions.
[0016] Another technical solution of the present invention is: A method for regulating the solubility of calcium sulfate in an ionic rare earth leaching solution is to adjust the solubility by adding sulfuric acid, and the solubility is increased by reducing the pH from 3-6 to 0.8-2; and the solubility is reduced when the pH from 0.8-2 is reduced to a sulfuric acid concentration of 0.8-1.2wt%. The leaching solution also contains Ca 2+ 50-800 mg / L, La 3+ 0.1-1 g / L.
[0017] The beneficial effects of the present invention are: In the membrane concentration process of rare earth leachate, in order to solve the membrane pollution problem caused by calcium sulfate scaling, the present invention proposes a new process for membrane concentration under low pH conditions: (1) Under low pH conditions, the solubility of calcium sulfate increases, which helps to increase the concentration multiple; (2) Under low pH conditions, the positive charge of the membrane surface increases, which helps to improve the retention of rare earth ions; (3) However, low pH places higher requirements on the stability of membrane materials. By studying the permeability selectivity of different membrane materials and combining the Hermia model, the effects of different membrane process parameters and feed liquid characteristics on calcium sulfate scaling were analyzed, and finally the optimal membrane concentration process was formed. It provides a new idea for the efficient membrane concentration of rare earth leachate, helps to improve the efficiency of rare earth extraction and enrichment, reduce the investment cost of equipment, and promote the further development of the ionic rare earth mining industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 :Retention data of La2(SO4)3 and Ce2(SO4)3 by different commercial membranes.
[0020] Figure 2 : Changes in MNF normalized flux, retention rate and ion concentration in solution.
[0021] Figure 3 : Changes in normalized flux and retention rate of MNF-Acid and changes in ion concentration in solution.
[0022] Figure 4 : Changes in Duracid normalized flux, retention rate and ion concentration in solution.
[0023] Figure 5 : Changes in normalized flux and retention rate of TW-30 and changes in ion concentration in solution.
[0024] Figure 6 : SEM images of membrane surface before and after commercial membrane concentration.
[0025] Figure 7 : Comparison of calcium ion concentration on the membrane surface after the experiment.
[0026] Figure 8 : Duracid normalized flux variation curve during the concentration process of simulated rare earth leaching solutions with different concentrations.
[0027] Fig. 9 : Curve diagram of the performance changes of MNF-Acid and Duracid membranes during the rare earth leachate concentration process under pH=1 (feed solution: 1.4 g / L Mg 2+ , 0.4 g / L La 3+ , 0.4 g / L Ca2+ ), where (a) the membrane flux, ion retention rate and ion concentration changes in the concentrate of MNF-Acid (b) the membrane flux, ion retention rate and ion concentration changes in the concentrate of Duracid.
[0028] Fig.10 : SEM images of membrane surface before and after MNF-Acid and Duracid experiments.
[0029] Fig.11 : Curves of changes in normalized flux, ion retention rate and ion concentration in the concentrated solution of MNF-Acid membrane under pH=5.8 conditions.
[0030] Fig.12 : Curve diagram of normalized flux, ion retention rate and ion concentration in the concentrated solution of MNF-Acid membrane under pH=3 condition.
[0031] Fig.13 : Curves of changes in normalized flux, ion retention rate and ion concentration in the concentrated solution of MNF-Acid membrane under pH=1 conditions.
[0032] Fig.14 : The results of the membrane module concentration test under different pH conditions, including (a) the normalized flux of the membrane module during the concentration process under pH=5.8 and the change of ion concentration in the concentrate; (b) the normalized flux of the membrane module during the concentration process under pH=1 and the change of ion concentration in the concentrate. DETAILED DESCRIPTION
[0033] The reagents used in this article include anhydrous magnesium sulfate, calcium sulfate dihydrate, anhydrous lanthanum sulfate, cerous sulfate, sodium hydroxide, anhydrous sodium sulfate, anhydrous sulfuric acid and hydrochloric acid; the real rare earth leaching solution was taken from a rare earth mine and pre-treated by ultrafiltration; the ultrapure water was homemade in the laboratory.
[0034] Table 1 Main ion components of real rare earth leaching solution
[0035] Six commercial membranes were used in the experiment: DF60 (Beijing OriginWater Technology Co., Ltd.), DK (Ge Osmonics), MNF (Nanjing Weihua Membrane Technology Co., Ltd.), TW-30 (Dow Chemical Company), Duracid (Veolia), and MNF-Acid (Nanjing Weihua Membrane Technology Co., Ltd.).
[0036] A laboratory-made cross-flow apparatus was used to evaluate the permeation and separation performance of the membrane. The effective membrane area was 12.56 cm 2, operating at 6 bar, the separation performance of the nanofiltration membrane is determined by the feed side (C p ) and the permeate side (C f ) is jointly determined by the solute concentration. The concentration of inorganic salts is tested using a conductivity meter and a plasma emission spectrometer, and the solute rejection (R, %) is calculated using formula (1): (1) The solubility of calcium sulfate under different conditions was determined by the saturated shake flask technique. Excess calcium sulfate was added to a solution with a known pH value and lanthanum ion concentration, and the solution was stirred on a magnetic stirrer for 24 hours. When the solution was saturated, the undissolved calcium sulfate in the solution was removed by filtration, and the clarified solution was taken to test the calcium ion concentration by plasma emission spectrometry. The solubility of calcium sulfate under different conditions was obtained by formula (2).
[0037] (2) In the formula Ca 2+ Molar mass, g / mol; is the molar mass of CaSO4, g / mol.
[0038] In a self-made cross-flow device, the simulated rare earth leachate was concentrated under different pH conditions (5.8, 3, 1), different pressures, and different feed flow rates. The flux was recorded once every hour and the normalized flux ( J ) Visually observe the changes in the permeation flux of the membrane; In addition to directly observing the surface contamination of the membrane after the test through an electron microscope, the residual calcium ions on the surface of the membrane after the test were completely removed by ultrasound and fully dissolved in ultrapure water. The Ca ions in the solution were tested by ICP. 2+ The concentration of calcium ions can be calculated by formula (3) to obtain the distribution density of calcium ions on the membrane surface.
[0039] (3) In the formula is the distribution density of calcium ions on the membrane surface, mg / cm 2 ; is the content of calcium ions in ultrapure water, mg; A S is the surface area of the membrane selected during ultrasound, cm 2 .
[0040] Calculation of membrane fouling using the Hermia model Hermia established a mathematical model to explain the reason for the reduction in flux. The original Hermia model is only applicable to dead-end filtration under constant pressure conditions, while there is shear force in cross-flow filtration, so when analyzing the membrane fouling mechanism, it is necessary to consider the change in permeate flux caused by the cross-flow velocity. Therefore, Field et al. [Non-patent document 1] modified this model to explain the membrane fouling mechanism in cross-flow filtration. After fitting the filtration flux data according to the model, the type of fouling with the largest correlation coefficient was found. The modified Hermia model is formula (4-7).
[0041] Fully pore-blocked model: (4) Standard pore plugging model: (5) Mesopore Blockage Model: (6) Pie Layer Model: (7) in k is the kinetic rate of different membrane fouling models, J * is the solution flux contributed by the cross-flow velocity, J is the membrane permeation flux.
[0042] Rare earth ion rejection performance of commercial membranes Since real rare earth leachate is usually weakly acidic (pH ≈ 4), the lanthanum sulfate and cerium sulfate (500 ppm) rejection experiments of commercial membranes were all carried out under the condition of pH = 4. Figure 1 ), the rejection rates of DF60 and DK membranes for lanthanum sulfate and cerium sulfate are relatively low. Specifically, the rejection rates of DF60 for lanthanum sulfate and cerium sulfate are 95.31% and 96.36%, respectively, and the rejection rates of DK membrane for these two substances are 98.31% and 95.22%, respectively. In contrast, the rejection rates of MNF, TW-30, Duracid and MNF-Acid membranes for lanthanum ions and cerium ions are all over 99%. The efficient interception of rare earth ions by these membranes ensures the recovery rate and concentration efficiency of rare earth leachate. Therefore, according to the screening of the interception rate, MNF, TW-30, Duracid and MNF-Acid membranes are more suitable for the concentration of rare earth leachate.
[0043] Comparison of anti-fouling performance of commercial membranes Due to the low grade of rare earth ore, the rare earth ion concentration in the real rare earth leachate is usually 0.2 g / L. In order to reduce the production pressure of the extraction section, a higher concentration of rare earth leachate is required in production. This experimental design simulates the process of concentrating the real feed solution by 2 to 3 times to explore the effect of membrane fouling on membrane flux. The starting rare earth ion (La 3+ ) concentration is 0.4 g / L (C ca 2+ =0.4 g / L,C Mg 2+ =1.4 g / L), and the cross-flow rate was set to 90 L / h.
[0044] The performance differences of four commercial membranes, TW-30, MNF, MNF-Acid and Duracid, in the process of concentrating lanthanum ions in rare earth leachate to about 0.6 g / L were compared. Figure 2 , Figure 3 , Figure 4 and Figure 5As shown. The study found that the four commercial membranes maintained a high rejection rate for rare earth lanthanum ions during the concentration process. MNF retained more than 98% of lanthanum ions and calcium ions, and TW-30, MNF-Acid and Duracid retained more than 99% of lanthanum ions. TW-30 and MNF-Acid retained more than 97% of calcium ions, and Duracid retained more than 98% of calcium ions. However, the flux of all membranes decayed over time, which may be due to the aggravation of concentration polarization caused by concentration and the scaling of calcium sulfate on the membrane surface. Take the rare earth concentration process of MNF membrane as an example: First, in the rare earth leachate, affected by magnesium sulfate, the saturated calcium ion concentration is about 0.51 g / L. Theoretically, when the recovery rate is about 25% (about 4 hours of concentration), the calcium ion concentration in the leachate is about 0.53 g / L, which exceeds the saturated calcium ion concentration, but in fact, the flux did not show a significant decrease after 4 hours, because there is an induction period for the precipitation of calcium sulfate. As the solution continued to concentrate, after 7 hours, the recovery rate reached about 33%, and the calcium ion concentration reached 0.64 g / L, far exceeding the saturated calcium ion concentration under this condition (0.51 g / L), and the calcium ion concentration increase rate decreased, which may be because the calcium ions scaled and precipitated on the membrane surface in the form of calcium sulfate. For other commercial membranes, the calcium ion concentration in the solution of Duracid showed a significant decrease in the late stage of concentration, proving the crystallization and precipitation of calcium sulfate. However, the TW-30 and MNF-Acid membranes showed a significant decrease in calcium ion concentration in the late stage of concentration, which may be because the growth rate of ion concentration caused by concentration accelerated in the late stage of concentration, and the high flux caused the increase rate of calcium ion concentration in the solution to be greater than the decrease caused by the precipitation of calcium sulfate. Similarly, during the concentration process, the flux of the four membranes decreased significantly, among which the flux of TW-30 decreased the most, about 32% of the initial flux.
[0045] By comparing the SEM images before and after the concentration process ( Figure 6 ), and found that the membrane surface after concentration was significantly contaminated. The calcium ions remaining on the membrane surface after the test were fully dissolved in ultrapure water by ultrasound and analyzed by ICP. In order to exclude the residue on the membrane surface caused by adsorption, the Ca ions on the membrane surface after being immersed in the simulated rare earth leaching solution for the same time were tested. 2+ with La 3+ The test results show (Table 2) that the membrane surface after immersion contains almost no Ca 2+ with La 3+ , which can eliminate the Ca on the membrane surface caused by ion adsorption 2+ The residual calcium ion concentration on the surface of TW-30, which has the largest flux attenuation, is the highest (1.25 mg / cm 2), Duracid, which has the least flux attenuation, has the lowest residual calcium concentration (0.60 mg / cm 2 ), proving that the attenuation of membrane flux is directly related to membrane fouling caused by calcium sulfate. In conclusion, in the concentration process of simulated rare earth leachate, all four membranes showed significant flux attenuation and obvious membrane surface fouling.
[0046] Table 2 Residual ion concentration on membrane surface
[0047] Note: 1. The detection limit can reach ng / L Rare earth leaching solution simulation experiment When the solubility of calcium sulfate in the solution reaches saturation, it will cause rapid scaling of inorganic salts on the membrane surface, leading to the attenuation of membrane flux. Mg 2+ =1.75 g / L, C Ca 2+ =0.5 g / L, C La 3+ =0.5 g / L) and unsaturated calcium sulfate (C Mg 2+ =1.4 g / L, C Ca 2+ =0.4 g / L, C La 3+ =0.4 g / L). Figure 7 As shown in the figure, when using Duracid membrane for concentration, the membrane flux of saturated calcium sulfate solution decayed significantly within the first hour and showed a gradually decreasing trend. The main reason for this was that saturated calcium sulfate was rapidly adsorbed and deposited on the membrane surface. The membrane flux decay trend of unsaturated calcium sulfate solution was significantly smaller than that of saturated calcium sulfate solution. Therefore, calcium sulfate scaling is a key factor restricting the efficient concentration of rare earth leachate, and increasing the saturated solubility of calcium sulfate in the solution is an effective strategy to increase its concentration multiple.
[0048] The solubility of calcium sulfate is affected by temperature, pH, and other ion concentrations. The solubility of calcium sulfate is 2.02 g / L, 2.10 g / L, and 2.01 g / L at 20, 40, and 60 °C, respectively. Therefore, the solution temperature has little effect on the solubility of calcium sulfate, and the increase in temperature will accelerate the precipitation of calcium sulfate on the membrane surface, aggravating the generation of membrane fouling. Therefore, in the exploration of membrane technology, the main focus is on the effects of different pH and different ion concentrations on the saturated solubility of calcium sulfate (Table 3). Under the same pH value, the solubility of calcium sulfate is negatively correlated with the concentration of magnesium sulfate and positively correlated with the concentration of lanthanum sulfate. There is a common ion effect, and the solubility of CaSO4 decreases with the increase of MgSO4 concentration. On the contrary, rare earth ions will adsorb on the surface of calcium sulfate crystals, hindering the growth of calcium sulfate crystals, so rare earth ions can increase the solubility of CaSO4. As the concentration of lanthanum ions increases from 0.05 g / L to 0.40 g / L, the solubility of calcium sulfate increases from 1.97 g / L to 2.55 g / L. As the concentrations of rare earth ions and magnesium ions continue to rise during the concentration of the rare earth leaching solution, the effect of changes in the concentrations of lanthanum sulfate and magnesium sulfate on the solubility of calcium ions becomes difficult to predict.
[0049] Since the inorganic salts in this experiment are all sulfates, in order to avoid the influence of other ions, the pH value of the solution was adjusted using concentrated sulfuric acid. 2+ The concentration is 1.4 g / L, La 3+ When the concentration is 0.4 g / L, the solubility of calcium sulfate increases with the decrease of the pH value of the solution (1.73 g / L at pH = 5.8, 2.79 g / L at pH = 1). This is because the H + It will adsorb on the surface of calcium sulfate crystals and form bonds with the oxygen atoms on the surface, thereby reducing the specific surface free energy of the crystal surface and hindering the Ca 2+ The aggregation of H + With SO4 2- HSO4 produced by the interaction - Will reduce SO4 2- electronegativity, thereby reducing SO4 2- However, when the content of concentrated sulfuric acid was further increased to 1 wt%, the solubility of calcium sulfate decreased to 2.44 g / L. This may be due to the high concentration of H2SO4 ionizing to produce a large amount of H + With SO4 2- , causing Ca 2+ With SO4 2- The spacing between Ca 2+ With SO4 2-The solubility of calcium sulfate will decrease as the acidity of the solution increases (i.e., the pH value decreases). However, when the concentration of sulfuric acid is too high, it will in turn lead to a decrease in the solubility of calcium sulfate. Therefore, it is an effective strategy to increase the solubility of calcium sulfate by adjusting the pH value and thus alleviate the formation of membrane fouling.
[0050] Table 3 Solubility of calcium sulfate under different conditions
[0051] Effect of different pH values on membrane fouling Under the condition of pH=1, the saturated calcium ion concentration is high (0.82 g / L). Therefore, based on the two acid-resistant membranes Duracid and MNF-Acid, rare earth leaching solution was concentrated under pH=1, and the flux changes of the two membranes were compared when the rare earth leaching solution recovery rate was 33% ( Fig. 9 The flux of MNF-Acid decayed by 19%, while the decay under pH=5.8 was 28%. Combined with the SEM images before and after concentration ( Fig.10 ), it can be seen that the membrane fouling is significantly alleviated compared with the pH=5.8 condition. This shows that the reduction of feed pH effectively alleviates membrane fouling. The Duracid membrane flux shows a flux attenuation of about 25% relative to the initial flux, and its attenuation amplitude is higher than that of MNF-Acid.
[0052] In order to clarify the mode of membrane pollution and improve the cleaning effect, the membrane pollution under different operating parameters was explored, and the membrane pollution was considered by the Hermia model, which describes four classic forms of membrane pollution: full pore blockage model, intermediate pore blockage model, standard pore blockage model and cake layer formation model. These models can intuitively reflect the influence of different pollution mechanisms in the filtration process. For the complex system of rare earth leachate, by directional analysis of the main stages of membrane pollution and combining real data, the pollution process of pollutants on the membrane surface can be more accurately described. The main mechanism of the initial formation of pollutants was explored. Cake layer pollutants have not yet formed, so the membrane pollution is calculated only from three aspects: full pore blockage model, intermediate pore blockage model, and standard pore blockage model.
[0053] First, the effect of solutions with different pH values on membrane fouling was analyzed. In the process of concentrating the lanthanum ion concentration in the solution to about 0.65 g / L, as the pH value decreased, the main mode of membrane fouling changed from standard pore blockage to intermediate pore blockage, and finally to complete pore blockage. This may be because calcium sulfate crystals form on the membrane surface earlier under the condition of pH = 5.8, but due to the low concentration, it is difficult to form large pieces of calcium sulfate, so it is easily carried away by the cross-flow solution, and the Ca sulfate that enters the membrane pores 2+ With SO42- The calcium sulfate crystals formed by the combination are not easy to be taken away. As the concentration progresses, the blockage of the standard pores inside the membrane pores intensifies. This kind of pollution inside the membrane pores is irreversible, so it is not conducive to the recovery of flux after the membrane is cleaned. Under the condition of pH=3, the flux was concentrated for 7 hours with almost no attenuation. At this time, the calcium ion concentration in the solution and on the membrane surface was high, and then the membrane flux decayed significantly. This is because the higher concentration accelerated the growth rate of crystals precipitated on the membrane surface, causing the blockage of the intermediate pores. Under the condition of pH=1, the flux showed a significant attenuation later, and the concentration on the membrane surface was higher at this time. When calcium sulfate crystals began to precipitate, the crystals grew faster, resulting in complete pore blockage.
[0054] Performance changes of MNF-Acid membrane during rare earth leaching solution concentration under different pH conditions (feed solution: 1.4 g / L Mg 2+ , 0.4 g / L La 3+ , 0.4 g / L Ca 2+ The cross flow rate is 90 L / h, and the yellow scattered points represent the Hermia model fitting segment). The curves are as follows Figure 11 to Figure 13 shown.
[0055] Table 4 Hermia model fitting results of membrane fouling process under different pH conditions
[0056] It can be seen from Table 4 that when the pH value is low, it belongs to the complete pore blockage type. As the pH value increases, the pollution type gradually changes to intermediate pore blockage and standard pore blockage.
[0057] Therefore, a judgment method can be obtained, that is, as the pH value decreases, the type of membrane fouling changes from standard pore blockage to intermediate pore blockage and complete pore blockage. Mg 2+ =1.05 g / L, C Ca 2+ =0.3 g / L, C La 3+ =0.3 g / L) to test the effect of pH value change on membrane fouling type, and similar results were obtained, as shown in Table 5, which proves the suitability of the above judgment method. Combining various experiments, it can be seen that under the condition of pH=1, due to the high solubility of calcium sulfate, when it begins to precipitate, the pollutants will form larger particles due to their high concentration and fast growth rate, so the type of pollution formed is complete blockage; however, it is precisely because the particles only exist on the membrane surface and are easily washed away by cross-flow, so the membrane pollution is relatively light.
[0058] Table 5 Hermia model fitting results of membrane fouling process under different pH conditions
[0059] It was found that changing the pH value of the solution is most likely to alleviate the impact of calcium sulfate precipitation on membrane fouling during the concentration process. Therefore, the existing process was improved, and the pH value of the rare earth leaching solution was adjusted to 1 before membrane concentration. The research results showed that as the pH of the solution decreased, the flux attenuation caused by membrane fouling was significantly alleviated, and the generation of irreversible pollution could be effectively reduced. In addition, because the surface charge of the membrane changed from negative to positive, the Donan effect was enhanced, and the membrane showed a higher rare earth ion retention efficiency. Pilot test of rare earth concentration commercial membrane module To verify the practical application of this method, an amplification experiment was carried out using the 1812 MNF-Acid membrane module. The performance changes of the membrane module concentration process under different pH conditions were tested using simulated rare earth leachate. The results showed that the rare earth ion concentration could be increased by more than 3 times under both conditions, but there were significant differences in the impact on membrane fouling. After 3 cycles of testing at pH=5.8, the flux was not fully recovered, and the loss was about 8.5% of the initial flux, which indicates that concentration under this condition is prone to irreversible attenuation of membrane flux, which is consistent with the Hermia model fitting. In addition, at 35 minutes of concentration, the recovery rate was about 45%, and the theoretical and actual values of lanthanum ion and calcium ion concentrations were not much different; at 65 minutes of concentration, the recovery rate was about 70%, and the theoretical calcium ion concentration was deviated from the actual concentration, proving that the precipitation time of calcium sulfate was between 35 and 65 minutes. After three cycles of testing at pH = 1, the flux showed only a slight loss of about 1.1%, indicating that the concentration under this condition significantly reduced the impact of irreversible fouling on the membrane, and the theoretical calcium ion concentration was not much different from the actual concentration, proving that the precipitation of calcium sulfate was alleviated.
Claims
1. A method for concentrating and separating ionic rare earth leachate by nanofiltration membrane, characterized in that: The method comprises the following steps: obtaining rare earth leaching solution, lowering the pH value, and concentrating the solution using a nanofiltration membrane.
2. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: The rare earth ion concentration in the rare earth leaching solution is in the range of 10-1000 mg / L.
3. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: Rare earth ions refer to cations of one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium or yttrium.
4. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: The leaching solution also contains Ca 2+ 50-800 mg / L and / or Mg 2+ 200-3000mg / L.
5. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: Lowering the pH means lowering the pH to 0.5-4, preferably 0.5-3.
6. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: In the process of lowering the pH, sulfuric acid, hydrochloric acid or nitric acid is used for adjustment.
7. The method for concentrating and separating ionic rare earth leachate by nanofiltration membrane according to claim 1, characterized in that: The pressure range during the concentration process of the nanofiltration membrane is 3-10 bar.
8. A method for predicting membrane pollution type during nanofiltration membrane concentration of ionic rare earth leachate, wherein the membrane pollution type is determined by fitting the nanofiltration membrane flux attenuation curve data through the Hermia pollution model and taking the pollution type with the maximum correlation coefficient value; comprising the following steps: when the pH value range of the leachate is 5-6, it is standard pore blockage; if the pH value range of the leachate is 2.5-3.5, it is intermediate pore blockage; if the pH value range of the leachate is 0.8-1.2, it is complete pore blockage.
9. A method for determining membrane contamination during the concentration of ionic rare earth leaching solution by a nanofiltration membrane, the method being used to determine the surface contamination amount of the nanofiltration membrane after concentration; comprising the following steps: dissolving the contaminants remaining on the surface of the nanofiltration membrane after concentration in water, and detecting the content of the contaminant ions in the water; Furthermore, a nanofiltration membrane is immersed in the same raw material solution, and then the immersed nanofiltration membrane is immersed in water to detect the pollutant ion content in the water. If the pollutant ions can be detected, it is determined that there is ion adsorption contamination on the membrane surface, and if the pollutant ions cannot be detected, it is determined that there is no ion adsorption contamination on the membrane surface. The pollutant is calcium sulfate, and the pollutant ions are calcium ions.
10. A method for regulating the solubility of calcium sulfate in an ionic rare earth leachate, wherein the solubility is increased by adding sulfuric acid to reduce the pH from 3-6 to 0.8-2, and the solubility is decreased when the pH from 0.8-2 is reduced to a sulfuric acid concentration of 0.8-1.2 wt %. The leachate also contains Ca 2+ 50-800 mg / L, La 3+ 0.1-1 g / L.
Citation Information
Cited By
Method for determining in-membrane concentration of membrane inlet side in micro-pollutant cross-nanofiltration membrane mass transfer process
CN121856103A